Extracellular Vesicles Derived from Mesenchymal Stem Cells Recover Fertility of Premature Ovarian Insufficiency Mice and the Effects on their Offspring. (4th May 2020) - Liu, Conghui; Yin, Huiqun; Jiang, Hong; Du, Xin; Wang, Cunli; Liu, Yingchun; Li, Yu; Yang, Ziling
It has been reported that extracellular vesicles (EVs) derived from human umbilical cord mesenchymal stem cells (HUCMSCs) can promote the proliferative and secretive functions of granulosa cells. In vivo study further demonstrated that EVs derived from HUCMSCs can not only promote the angiogenesis of ovarian tissue but also restore the function of an ovary of chemically induced premature ovarian insufficiency (POI) mice. However, no study investigates the effects of HUCMSCs derived EVs on fertility recovery of POI mice and evaluating their offspring. This study investigates the effects of HUCMSCs derived EVs on fertility recovery and the cognitive function of their offspring. A POI model was established by intraperitoneal injection of cyclophosphamide (CTX) and busulfan (BUS), and randomly divided into EVs-transplantation group (a single injection of 150 µg EVs proteins which suspended in 0.1 ml phosphate buffer saline [PBS] via tail vein), POI group (a single injection of 0.1 ml PBS via tail vein), and normal control group (a single injection of 0.1 ml PBS via tail vein without intraperitoneal injection of CTX and BUS). After EVs treatment, not only the ovarian function of POI mice recovered but also the fertility increased with less time to get pregnant, evaluating by in vitro fertilization and mating test. Cognitive behaviors of the offspring were similar among the three groups through the Y-maze test and novel object recognition task. An anti-apoptotic effect was identified through immunohistochemistry, real-time polymerase chain reaction and western blot. These findings indicate that HUCMSCs derived EVs can improve the fertility of POI mice without adverse effects on the cognitive behavior of their offspring, highlighting the potential value of EVs to be a cell-free therapy for patients suffering from POI.